Environmental indicators of banana production in Brazil: Cavendish and Prata varieties - Coltro, Leda (2019)
There are relatively few studies in the area of Life Cycle Assessment (LCA) concerning tropical perennial agricultural products, although agricultural activities in 2005 accounted for 10e12% of the total global anthropogenic emissions of greenhouse gases (GHGs) and most N2O emissions. Furthermore, the wide diversity of these products contrasts with reduced available environmental data in Brazil. In 2012, bananas were ranked in the twelfth position on the list of commodities in Brazil and accounted for an income of US$ 1,943,869 thousand dollars. Most of the bananas produced are consumed domestically, but exports are growing. The Prata banana variety, for example, began to be exported to Europe recently. Therefore, the aim of this study is to determine environmental indicators for two varieties of banana produced in Brazil e Cavendish and Prata e in order to promote these products to consumers. This study was developed in accordance with the recommendations of the international standards ISO 14,040 and 14,044. The scope of the study was to evaluate banana production systems located at Ribeira Valley, S~ao Paulo State and North of Minas Gerais, which is the main producer of the Prata variety. The temporal coverage was from 2011 to 2014. The functional units adopted were 1 ha of banana orchard and 1 kg banana available at retail. The global warming potential (GWP100), primary energy demand (PED), abiotic depletion (AD), eutrophication potential (EP), acidification potential (AP), land use (LU), total freshwater use (TFW), blue water use (BW), terrestrial ecotoxicity potential (TETP) and human toxicity potential (HTP) of these bananas were estimated. The Prata variety showed lower GWP than Cavendish (4484.92 vs 5762.00 kg CO2-eq ha 1) due to using less nitrogen fertilizers and shorter distances, although this crop is irrigated and consequently consumes electricity. On the other hand, the Prata variety showed higher BW than Cavendish (14,800.36 vs 5300.44m3 ha 1) due to the irrigation of this crop. Therefore, having the environmental indicators, producers can make improvements in crop management to reduce the environmental impact of the products. Moreover, indicators can be used for promoting the products to local and overseas consumers.